Mesiodens: a case report - Giovanetti, Karina; Sigua-Rodriguez, Eder Alberto; Pacheco, Larissa; Portela-Figueiredo, Evandro; Albergaria-Barbosa, Jose Ricardo (Revista Facultad de Odontología Universidad de Antioquia, 2016)
Mesiodens are supernumerary teeth, commonly seen in the maxillary midline. Given their high frequency, dentist should be aware of the signs and symptoms of mesiodens and their appropriate treatment. This case report describes an 8-year-old girl with a radiographic image suggesting two unerupted mesiodens between the central incisors on the palate. The intraoral examination showed swelling in the anterior palatal region with no mucosa alteration. The supernumerary teeth were diagnosed by periapical radiograph and computed tomography. The objective of this study is to present the clinical importance and use of diagnostic images, such as periapical radiograph (Clark technique) or tomography.